2017
DOI: 10.21767/2254-6081.1000128
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Assessment of Children with Acute Lymphoblastic Leukemia

Abstract: Background: The high prevalence of malnutrition in adult and pediatric cancer patients has been appreciated for decades and continues to be documented. Although the prognostic significance of nutritional status among patients with cancer remains controversial, it is generally accepted that the nutritional support is an important aspect of medical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(21 reference statements)
0
0
0
Order By: Relevance
“…Several other ALL studies also reported higher prevalences in males than females. 7,13,14 The mean age was 7.5 years in the well-nourished group and 6.9 years in the malnourished group. A study in Semarang reported a median age of 6.58 years in childhood ALL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other ALL studies also reported higher prevalences in males than females. 7,13,14 The mean age was 7.5 years in the well-nourished group and 6.9 years in the malnourished group. A study in Semarang reported a median age of 6.58 years in childhood ALL.…”
Section: Discussionmentioning
confidence: 99%
“…6 Nutritional supportive care is a medical modality associated with improved tolerance to chemotherapy, increased survival rate and quality of life, as well as decreased risk of infection in children undergoing anticancer therapy. 7 Induction is an important chemotherapy phase, in which maximum destruction of leukemic cells occurs. 8 Therefore, nutritional status evaluation at the initial diagnosis and its possible association with induction phase outcome is needed.…”
mentioning
confidence: 99%
“…al. [16] which showed that most patients with acute leukemia had excess fat reserves during chemotherapy, which is a result of corticosteroid therapy that causes alteration in fat metabolism, which had a net effect of increasing body fat and redistribution of body fat causing truncal obesity [19]. *One of the limitations of this study DXA was not used for the assessment of body composition, not available in this center.…”
Section: Mid-upper Arm Fat Area For Age In Percentile (During Chemoth...mentioning
confidence: 95%